SISTEM INFORMASI PENDATAAN INDUSTRI KECIL DAN MENENGAH (IKM) DI PROVINSI JAMBI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI JAMBI: Department of Industry Trade, Industrial Data Processing application, web - Nelmiyanti, Putri; -, Afrizal (LP2M Universitas Nurdin Hamzah, 2019)
This study discusses the information system of Small and Medium Industries is a sector that has various important roles in the economy whose founders are based on one's initiative. Application of Industrial Processing at the Web-based Office of Trade Industry Information System Study Program, The development of highly sophisticated and modern computer technology will make it easier for us to do data processing that can save time, space and costs. Processing data and information quickly, precisely and efficiently is an important thing that is needed for institutions or agencies, one of which is the Industry Sector of the Department of Trade, Jambi Province. Department of Industry and Trade of Jambi Province. A better data processing and delivery system is a necessity that cannot be delayed anymore. To overcome the existing problems, we need a sophisticated and computerized application so that the industrial data processing can be done accurately and accurately. The Department of Industry and Trade of Jambi Province will utilize technological advances in data processing and information delivery online. In making industrial data processing applications researchers use the PHP programming language, and use MySQL databases as database servers. Industrial data processing applications are focused on web-based technology.